PENGUATAN PERKEMBANGAN ANAK MELALUI ALUNAN LAGU PENGANTAR TIDUR “DINDANG BANJAR” - Rusma Noortyani; Mutiani Mutiani; Syaharuddin Syaharuddin; Jumriani Jumriani; Ersis Warmansyah Abbas (Khazanah: Jurnal Studi Islam dan Humaniora, 2021)
Abstract: Literature leaves a deep meaning that can be taken for life. One of the literary works in question is a local literary work, namely Dindang Banjar. In particular, the existence of the Banjar walls that are still maintained today makes it interesting to study. The Dindang Banjar can be called a song when you put your child to sleep. Chanting through the lyrics of the Dindang Banjar is delivered with great affection and deep love from parents to children. This study aims to describe the implementation of the advice in the lyrics of the Banjar songs. The descriptive qualitative is used for the method because it produces data and analysis in the form of phenomenon descriptions. Data collection is used through observation, interview, and documentation techniques. The results found that the lyrics came from the sincere hearts of parents and have a charm that is second to none into the soul of a child. Dindang Banjar implies values, such as; honesty, persistence, and intelligence. This lyric contains praise to Allah SWT, salawat to the Prophet Muhammad, good prayers from parents, parents' hope that children have faith, obey parents, keep away from cheating and feeling lazy, advice there is no sense of resentment and don't there is jealousy, advice away from cheating and keep jealousy. Even though the child who was sung was not yet understood, the message was already heard. Later in its growth, the child will hear the advice in the lyrics of the Dindang Banjar.Keywords: Literature, Dindang banjar, and value Abstrak: Karya sastra menyisakan makna mendalam yang dapat diambil untuk kehidupan. Satu diantara karya sastra yang dimaksud adalah karya sastra lokal yakni Dindang Banjar. Secara khusus, keberadaan Dindang Banjar yang masih terpelihara sampai sekarang menjadikan hal menarik untuk diteliti. Dindang Banjar dapat disebut sebagai lagu saat menidurkan anak. Nyanyian melalui lirik Dindang Banjar disampaikan dengan penuh kasih sayang dan rasa cinta yang dalam dari orang tua kepada anak. Penelitian ini bertujuan mendeskripsikan implementasi nilai petuah dalam lirik Dindang Banjar. Metode yang digunakan dengan deskriptif kualitatif karena menghasilkan data dan analisis berbentuk deskripsi fenomena. Pengumpulan data digunakan melalui teknik observasi, wawancara, dan dokumentasi. Hasil penelitian memaparkan bahwa Dindang Banjar keluar dari hati yang tulus orang tua dan memiliki daya tarik yang tidak ada duanya hingga memasuki ke dalam jiwa anak. Dindang Banjar menyiratkan nilai-nilai, seperti; kejujuran, keteguhan, dan kecerdasan. Lirik ini berisi pujian kepada Allah S.W.T., salawat kepada Nabi Muhammad saw., do’a yang baik, harapan orang tua agar anak memiliki iman, patuh kepada orang tua, menjauhkan diri dari kecurangan dan rasa malas, petuah jangan ada rasa dendam dan jangan ada rasa iri, petuah jauhkan dari sifat curang dan jauhkan rasa dengki. Meskipun anak yang didendangkan itu belum mengerti, pesan itu sudah didengarnya. Kelak dalam pertumbuhannya anak memahami petuah dalam lirik Dindang Banjar tersebut.Kata kunci: Karya Sastra, Dinding Banjar, dan Nilai